The fatigue of impellers and blades. (April 2016) - Zhang, Ming; Liu, Yan; Wang, Weiqiang; Wang, Pengfei; Li, Jianfeng
Abstract: Impellers and blades are the key components of turbomachines, and fatigue is the main failure mode of impellers and blades. The status and progress of fatigue research on impellers and blades were systematically introduced through reviewing fatigue failures, numerical simulations of fatigue, and fatigue tests of impellers and blades in several typical turbomachines. High cycle fatigue caused by vibration was the main failure mechanism, and fatigue cracks usually initiated from the location of stress concentration. The resonance caused by the aerodynamic load was the main cause of fatigue failure of impellers and blades in a steady operating condition. The coupling of the meshless method and the finite element method and the combined fatigue test of actual impellers and blades are the developmental direction and research focus of the future. Highlights: The fatigue failures of impellers and blades including failure modes, dangerous positions, and failure reasons were reviewed. The numerical simulations of fatigue of impellers and blades were reviewed. The fatigue tests of impellers and blades especially vibration fatigue tests and combined fatigue tests were reviewed. We further proposed the developmental direction and key issues of fatigue research on impellers and blades.